1963
DOI: 10.1017/s0021859600011904
|View full text |Cite
|
Sign up to set email alerts
|

The effects of magnesium compounds and of fertilizers on the mineral composition of herbage and on the incidence of hypomagnesaemia in dairy cows

Abstract: 1. An experiment, lasting 3 years, was carried out to investigate the control of hypomagnesaemia on a medium-heavy loam soil in Northern Ireland, using as criteria herbage analysis and analysis of blood sera of grazing dairy cows.2. Applications of calcined magnesite and magnesian limestone as soil treatments raised the magnesium contents of herbage slightly but not to levels judged to be safe. Low blood sorum magnesium levels were recorded for cows grazing this herbage although no cases of tetany occurred.3. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1963
1963
1995
1995

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…experiment (Allcroft, 1960), 250-500 kg/ha calcined magnesite was found to be enough to prevent hypo-Previous experiments (Tinker, 1967;Draycott & magnesaemia, but in another experiment on a more Durrant, 1969) have shown that spring applica-alkaline soil it gave a much smaller response, tions of kieserite (MgSO 4 .H 2 O) largely prevented McConaghy et al (1963) showed that calcined magnesium-deficiency symptoms and increased magnesite slightly increased magnesium in herbage, sugar-beet yield where the soils contained small but was not sufficient to prevent a deficiency of amounts of exchangeable magnesium. During the magnesium in blood serum of dairy cows.…”
Section: Introductionmentioning
confidence: 94%
“…experiment (Allcroft, 1960), 250-500 kg/ha calcined magnesite was found to be enough to prevent hypo-Previous experiments (Tinker, 1967;Draycott & magnesaemia, but in another experiment on a more Durrant, 1969) have shown that spring applica-alkaline soil it gave a much smaller response, tions of kieserite (MgSO 4 .H 2 O) largely prevented McConaghy et al (1963) showed that calcined magnesium-deficiency symptoms and increased magnesite slightly increased magnesium in herbage, sugar-beet yield where the soils contained small but was not sufficient to prevent a deficiency of amounts of exchangeable magnesium. During the magnesium in blood serum of dairy cows.…”
Section: Introductionmentioning
confidence: 94%
“…Using commercial magnesite (MgO), Griffiths (1959) found that the Mg concentration of grass increased rapidly with a small increase in yield. Rook & Wood (1960) used 3140 kg/ha of calcined magnesite to double the mean level of Mg in grass, yet McConaghy et al (1963) using the same source found only a slight increase in Mg concentration. When Parr & Allcroft (1957) compared calcined magnesite with magnesian limestone supplying equivalent amounts of Mg, the Mg concentration of pasture was increased by 73 and 23% respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Similar findings were reported by Reith (1954) after 5 months with no response in yield from magnesian limestone, but over a 3-year period the Mg concentration in mixed herbage was increased by 55% over no lime or CaCO 3 treatments. Using magnesian limestone, Griffiths (1959) found an increase in both yield and Mg concentration, McConaghy et al (1963) found a slight increase in Mg concentration while Wolton (1960) found magnesian limestone to be a poor source of magnesium. In the face of so many conflicting reports we have compared the effects of several magnesium fertilizers on yield and Mg concentration of a mixed sward, and on exchangeable soil magnesium in a field experiment over three seasons.…”
Section: Introductionmentioning
confidence: 99%
“…Soils with finer textures, however, required substantially higher amounts of Mg. Todd therefore concluded that fertilization with Mg was economically impractical except on coarse textured soils, soils with a low pH, or soils with low K availability. McConaghy et al (1963) also concluded that fertilization of fine textured soils was ineffective in raising plant tissue concentrations of Mg. In this study he applied calcined magnesite and Mg-limestone.…”
Section: Soil Texturementioning
confidence: 99%